Pengaruh Video Tutorial Terhadap Hasil Belajar Melipat Serbet Siswa Kelas 11 Kuliner - Devy, Ananda Aulia; Kharnolis, Mein; Bahar, Asrul; Miranti, Mauren Gita (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2025)
The Independent Curriculum provides flexibility for teachers ini designing learning that is in accordance with the characteristics of students, one of which is in the napkin folding material in class XI Culinary at SMK Negeri 6 Surabaya. This study aims to determine the effect of the use of video tutorials on student learning outcomes in the cognitive, affective and psychomotor domains. The research method use is quantitative with a quasi-experimental design. Data collection techniques include tests and observations. Data analysis techniques use the independent t-test and effect size (Cohens'd). The results of the study showed: (1) Cognitive learning outcomes were in the very good category with a significance value of 0.000 and Cohens’d 0.050 (small). (2) Affective learning outcomes were in the very good category with a significance value of 0.000 and Cohens’d 10.8 (very large). (3) Psychomotor learning outcomes had a significance value of 0.000 and Cohens’d 7.09 (very large). It can be concluded that the use of video tutorials has a significant influence and has a large influence on student learning outcomes. Keywords: video tutorials, napkin folding, learning outcomes